Exploring disparities in malnutrition among under-five children in Nigeria and potential solutions: a scoping review - John, Collins; Poh, Bee Koon; Jalaludin, Muhammad Yazid; Michael, Godpower; Adedeji, Idris; Oyenusi, Elizabeth Eberechi; Akor, Blessing; Charles, Nkwoala C.; Buthmanaban, Vanitha; Muhardi, Leilani (Frontiers in Nutrition, 2024)
Introduction: Triple burden of malnutrition in children remains a significant public health issue. This scoping review aims to assess the information on undernutrition, micronutrient deficiencies and the quality of complementary feeding in various regions in Nigeria.Methods: A literature search was conducted using PubMed and Google Scholar databases from January 1, 2018 to January 31, 2023 to include studies focusing on 0 to 5 years old children in Nigeria, reporting data on nutritional status, nutrient deficiencies, and published in English.Results: 73 out of 1545 articles were included. Stunting remained alarmingly high ranging from 7.2% (Osun, South West) to 61% (Kaduna, North West), while wasting varied from 1% (Ibadan, North East) to 29% (FCT Abuja, Central) and underweight from 5.9% (Osun, South West) to 42.6% (Kano, North East), respectively. The overall prevalence of anemia and vitamin A deficiency ranged between 55.2% to 75.1 % and 5.3% to 67.6%, respectively. Low rates of achieving minimum dietary diversity and minimum meal frequency were reported across different states depicting the suboptimal quality of complementary feeding. The prevalence of overweight/obesity ranged from 1.5% (Rivers, South South) to 25.9% (Benue, North Central).Multiple early childhood malnutrition issues exist with a wide disparity across states in Nigeria, particularly in the Northern region. Targeted nutrition interventions must be implemented to improve the situation.